Patterns of self-disclosure and narcissim on facebook of first year Iloilo Doctors' college students. - Guyod, Maria Louisa Belle J.
Facebook gave way for the development of narcissistic behavior. Narcissism on Facebook has been defined on the basis of patters of self disclosure, frequency and content of Facebook activities. In the study, 18 college students were identified as subclinical narcissists basing on the scores in the NPI-16. In content analysis, the topics usually disclosed by these subclinical narcissists disclosed were of 1) family, 2) friends, 3) money, 4) school, 5) feelings, and emotions and 6) events. The results yielded low frequency on the Facebook activity (profile picture change, status updates and sharing) of the respondents. Also, in the study, narcissists did not project self-promotional and self-focused behaviors in Facebook. The study implies that narcissism is not evident in Filipino Facebook users.